(untitled) (LACCEI, 2024)
It is essential to understand bacterial succession during the development of dental caries and determine the microorganisms related to this disease. This work aimed to identify bacteria associated with cariogenic pieces and carry out an antibiogram assay. First, we isolated bacterial isolates using MALDI TOF-MS and species-specific PCR techniques. Next, we implemented an antibiogram test to evaluate antimicrobial susceptibility events in Streptococcus oralis, Staphylococcus epidermidis, and Bacillus cereus. Our results showed that the bacterial species frequently associated with cariogenic processes was S. oralis. The antibiogram analysis determined that the most effective antibiotic was streptomycin, with a minimal significant difference of 0.52. Furthermore, the phylogenetic reconstruction allowed confirming the identity of the Colombian isolates that were sequenced, corresponding to the species S. oralis. Finally, we describe the complex etiology of dental caries where not only one bacterial agent is related to the development of this pathology. It is a complex of species.